A retrospective analysis of anterior single dental implants - Demirkol, Nermin; Demirkol, Mehmet (Annals of Medical Research, 2021)
Aim: This retrospective study aimed to examine the demographic data of patients who underwent an intraosseous maxillary anterior single dental implant and the characteristic features of dental implants, including diameter/length, distribution of anatomic localization and implant failure.Material and Methods: Demographic data, including the distribution of dental implants according to age, gender and the age of 108 patients who underwent dental implant placement in the researchers’ clinic between 2009 and 2015 were obtained from archival records. Only patients with the loss of a single tooth in the anterior region of the jaws were included. Anatomic localizations, diameter/height characteristics and implant failure results of the dental implants were analyzed with descriptive statistical analysis. Results: Of 108 patients, 47 (36.7%) were males and 61 (63.3%) were females. A total of 120 dental implants were evaluated. The mean age of the patients was 35.4±15.63 years, ranging from 18 to 70 years. The ages of the second decade, particularly 18 or 19 years old, was the most placed dental implant (n=24, 25%). A total of 103 (85.8%) implants were surgically placed into the maxillary anterior region and 17 (14.2%) into the lower jaw. The most common implant diameter was 4.1 mm (17 patients, 14.1%) and the length was 14 mm (42 patients, 35%).Conclusion: This study showed that the dental implant treatment in the esthetic region was demanded immediately by the patients without any further bone resorption.Keywords: Dental implant; mandible; maxilla; esthetic zone.
Keywords: Dental implant; mandible; maxilla; esthetic zone.